Recent Advances in Atmospheric-Pressure Plasma Technology (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Plasma technology has arisen as a novel approach in the processing and manufacturing of novel materials in recent years. Due to its benefits, such as its superior sterilizing performance, low cost, and environmental friendliness, atmospheric pressure plasma has drawn the attention of researchers. As a result, atmospheric pressure plasma manufacturing in different configurations (plan parallel and jet plasma) is becoming more popular. The necessity to characterize these types of plasmas has greatly expanded as a result of its wide range of applications. Due to these factors, “Recent Advances in Atmospheric-Pressure Plasma Technology” Issue in the journal Applied Physics that brings together experts in all areas of experimental, computational, and theoretical research on atmospheric pressure plasmas. This Special Issue brings together cutting-edge new research on the fundamental characteristics of these plasmas as well as their applications in the fields of medicine, the food industry, agriculture, 3D printing, materials processing science, and even the automotive and aerospace industries. Despite the fact that we were only able to touch on a small percentage of the potential applications for plasma discharge, we nevertheless hope that readers will find this reprint to be interesting and that they will discover new angles for their own future research on plasma.